Supply chain water-reporting practices in the food, beverage and tobacco sector: a comparative study. Issue 3 (3rd April 2022) - Botha, Marthinus Jacobus; Middelberg, Susanna Levina; Oberholzer, Merwe
ABSTRACT: Companies are responsible for reporting not only their own water practices but also those of their suppliers. An evaluation of the supply chain water information in the sustainability and integrated reports of 49 food, beverage and tobacco firms listed on the JSE (South Africa), ASX (Australia) and Dow Jones Sustainability Index (DJSI) exchanges, respectively, was conducted. It was found that the companies fall short in their disclosure of consumption of water-related supply chain information. The firms listed on the DJSI and JSE outperformed the Australian companies. This paper presents and applies a novel water disclosure index of supply chain information.